A Dynamics-Constrained Rapid Path-Planning Method for Shipping in Arctic Waters - Sun, Youguo; Wu, Da; Zhang, Jinfen; Lang, Xiao; Ringsberg, Jonas; Mao, Wengang; Cui, Meng (2024)
The challenge of Arctic sea ice environments is crucial for Arctic shipping. To address this concern, we propose an innovative method for ship path planning to enhance navigation safety and efficiency in Arctic waters. Firstly, a 3D risk grid map for path planning is developed based on POLARIS. The JPS algorithm searches for key nodes on the 2D layers sliced from the 3D risk grid map with given risk values. Secondly, key nodes indicating different risk values are pruned to form a roadmap for path-finding. Then, the Dijkstra algorithm is employed to find the reference path yielding the lowest navigation risk from the roadmap. Finally, the ship's trajectory is optimized through optimal control to guarantee the ship's maneuver feasibility. Experiments are carried out to demonstrate the performance of the optimized trajectory, and the outcomes validate the proposed method, demonstrating its capability of rapidly planning safe and executable paths for Arctic shipping.